Welcome To International Seminars In Surgical Oncology - Singh-Ranger, Gurpreet (BioMed Central, 2004)
This editorial marks the launch of a new online journal for surgical and medical oncology. The internet has produced a profound shift in the way in which clinicians, researchers and patients seek, interpret and utilise medical information and research. The launch of our journal comes at a time when these changes are in a rapid phase of development and consolidation.